Synthesis and characterization of nickel selenide for high-performing electrocatalytic evolution - Sim, Xin Yi (2019)
Nickel Selenide samples were synthesized using an effective high-temperature solution-phase method. Differing temperature were used during the synthesis process to determine the best condition for the synthesis of Nickel Selenide. Scanning electron microscopy (SEM) reveals that 180 °C is the best temperature to attain uniform and monophase Nickel Selenide nanoparticles. X-ray diffraction (XRD) patterns also showed that the nanoparticles synthesized at 180 °C matches NiSe2 the closest. The resultant Nickel Selenide particles were tested for oxygen evolution reaction (OER) and had an over potential of and a Tafel slope of. In addition, the electrocatalyst maintains stable over a 12-hour working period. This method can be easily extended to other materials by simply changing the metal source (e.g., CoCl2, FeCl2, CeCl2) and the chalcogen source (e.g., S). Therefore, these results reveal that the solution-phase method is a facile and cost-effective method to produce reliable and high-performing transition metal chalcogenides for advanced electrocatalysts.